2011
DOI: 10.1183/09031936.00125010
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rho kinase isoforms in murine allergic airway responses

Abstract: Objective Inhibition of Rho-associated coiled-coil forming kinases (ROCKs) reduces allergic airway responses in mice. The purpose of this study was to determine the roles of the two ROCK isoforms, ROCK1 and ROCK2, in these responses. Methods Wildtype mice and heterozygous ROCK1 and ROCK2 knockout mice (ROCK1+/− and ROCK2+/− respectively) were sensitized and challenged with ovalbumin. ROCK expression and activation were assessed by Western blotting. Airway responsiveness was measured by forced oscillation. Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 48 publications
(71 reference statements)
4
53
0
Order By: Relevance
“…In animal models of allergic asthma, exposition to the allergen ovalbumin (OVA) induces ROCK activation in the lungs (Zhu et al, 2011 (Zhu et al, 2011). Moreover, ROCK2, but not ROCK1, is involved in mucous cell hyperplasia in the OVA model of allergic asthma (Kasahara et al, 2015).…”
Section: B Asthmamentioning
confidence: 99%
“…In animal models of allergic asthma, exposition to the allergen ovalbumin (OVA) induces ROCK activation in the lungs (Zhu et al, 2011 (Zhu et al, 2011). Moreover, ROCK2, but not ROCK1, is involved in mucous cell hyperplasia in the OVA model of allergic asthma (Kasahara et al, 2015).…”
Section: B Asthmamentioning
confidence: 99%
“…Data from animal models indicate that Rho-associated coiled-coil forming kinases (ROCKs), serine/threonine protein kinases activated by GTP-bound RhoA, may be involved in the pathogenesis of asthma (1-4). ROCKs have pleiotropic effects that can contribute to asthma, including the ability to augment smooth muscle contraction (5, 6), as well as effects on immune cell proliferation and migration (2, 7).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that both ROCK1 and ROCK2 contribute to the pathological features of allergic airways disease in mice (4). ROCK1 and ROCK2 deficient mice typically die either in utero or soon after birth (15, 16), but heterozygous mice (ROCK1 +/− and ROCK2 +/− mice) are viable (17, 18).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations